2020
DOI: 10.3390/pharmaceutics12060485
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Intranasal Niosomal In Situ Gel as a Promising Approach for Enhancing Flibanserin Bioavailability and Brain Delivery: In Vitro Optimization and Ex Vivo/In Vivo Evaluation

Abstract: Flibanserin (FLB) is a multifunctional serotonergic agent that was recently approved by the FDA for the oral treatment of premenopausal women with hypoactive sexual desire disorder. FLB is a centrally acting drug that has a low oral bioavailability of 33% owing to its exposure to the hepatic first-pass effect, as well as its pH-dependent solubility, which could be an obstacle hindering the drug dissolution and absorption via mucosal barriers. Thus, this work aimed at overcoming the aforementioned drawbacks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…Free-TQ had been taken by passive transport, while phytosomes had been taken by endocytosis. In addition, phytosomes containing abundant phospholipids could carry amphiphilic agents to cross the cell membrane resulting in high intracellular drug concentrations [ 36 , 37 , 38 ]. However, the optimized formula showed relatively-weak cytotoxic activity against EA.hy926 non-cancerous endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Free-TQ had been taken by passive transport, while phytosomes had been taken by endocytosis. In addition, phytosomes containing abundant phospholipids could carry amphiphilic agents to cross the cell membrane resulting in high intracellular drug concentrations [ 36 , 37 , 38 ]. However, the optimized formula showed relatively-weak cytotoxic activity against EA.hy926 non-cancerous endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The random distribution of the points within the limits in both the externally studentized residuals vs. predicted response and the residual vs. run plots indicated that neither constant error nor lurking variable that can influence the measured particle size existed. Additionally, the highly linear pattern displayed in the predicted versus actual globule size plot reflected good coincidence between the observed and anticipated values [ 55 , 56 ]. Regarding the measured particle size, the comparatively low calculated standard deviation indicated homogenous and uniform distribution of the formulated bilosomal dispersions.…”
Section: Discussionmentioning
confidence: 75%
“…The human pharmacokinetic study of AVA showed a lower initial plasma concentration than that of NPs, possibly due to the slow solubilization rate of raw AVA. After 1.5 h, the plasma concentration for raw AVA was lower than for PLGA NPs, due to the rapid metabolism and elimination of free AVA compared to the encapsulated AVA within the PLGA NPs [ 50 , 51 ]. The findings also revealed that optimized AVA-PLGA NPs significantly changed the pharmacokinetic profile, and improved the bioavailability of AVA by > 1.3 times than that of the raw AVA.…”
Section: Discussionmentioning
confidence: 99%